Ceramic dielectric material, preparation method thereof and multilayer ceramic capacitor prepared from ceramic dielectric material
The development of high-pressure, high-energy density ceramic capacitors using (Sr, Ca, Ba)TiO3 and Bi2O3·2TiO2 additives addresses the limitations of traditional power systems, achieving improved energy storage and thermal stability for high-frequency and high-voltage applications.
Patent Information
- Application Number
- CN202411623785.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional power systems face limitations in high-voltage applications, including restricted charging and discharging speed, complex design requirements for insulation and heat management, and a balance between energy density and efficiency, which hinders their ability to meet the demands of modern communication and defense systems.
A high-pressure, high-energy density ceramic capacitor is developed using a (Sr, Ca, Ba)TiO3-based ceramic material with Bi2O3·2TiO2 as an additive, processed through a combination of low-temperature liquid phase reactions and water heat treatment, followed by a multi-layer ceramic capacitor fabrication method involving ball milling, screen printing, layer pressing, and high-temperature sintering.
The solution significantly enhances the energy storage density and thermal stability of the capacitors, enabling them to meet the high-frequency and high-voltage requirements of modern systems while optimizing production costs and ensuring reliable performance.
Smart Images

Figure CN119613107A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic materials, and in particular relates to a ceramic dielectric material and a preparation method thereof, and a multilayer ceramic capacitor prepared by using the ceramic dielectric material. Background Art
[0002] In modern communication and weapon systems, the performance of high-power power supplies is crucial to the reliability and response speed of the overall system. These application scenarios often require the power supply to be able to achieve high-voltage rapid charging and discharging in a very short time to meet the needs of transient loads and improve the dynamic response capability of the system.
[0003] Traditional power supply systems have some limitations in design and implementation, which are mainly reflected in the following aspects:
[0004] Charge and discharge speed: The charge and discharge speed of existing power supply systems at high voltage is usually limited by the charging and discharging characteristics of capacitors, the response time of switching devices, and circuit design limitations. These limitations make it difficult for the system to meet the needs of fast response, especially when transient loads change frequently.
[0005] Challenges of high voltage technology: In high voltage applications, power supply equipment needs to have good insulation performance and stability. However, as the voltage increases, the selection of insulation materials, heat dissipation management and circuit layout become more complicated, making the design and implementation of the system more difficult.
[0006] Energy density and efficiency: Existing high-power power systems often have difficulty finding the best balance between energy density and efficiency. Although some new materials and technologies (such as supercapacitors and advanced power management ICs) have made some progress in improving energy density and efficiency, they are still insufficient in high-voltage and fast charging and discharging scenarios.
[0007] System integration and compatibility: Power systems for specific applications often need to be tightly integrated with other electronic devices or systems. Existing technical solutions may not be well compatible with these systems, resulting in a decrease in the overall system performance. Summary of the invention
[0008] In order to overcome the deficiencies and shortcomings of the prior art, the primary purpose of the present invention is to provide a method for preparing a high-voltage, high-energy storage density chip multilayer capacitor, which is prepared into a high-voltage, high-energy storage density capacitor by studying the powder used in ceramic capacitors and developing the research and development process. The implementation of the project can enable enterprises to successfully achieve mass production of related products, meet the application of specific weapons and equipment, change the pattern of similar products relying on imports, ensure national defense security, realize the localization of high-voltage ceramic capacitors, and improve the current development status of my country in this field. Therefore, the development of this project not only has strong social benefits, but also brings greater economic benefits.
[0009] The primary purpose of the present invention is achieved through the following technical solutions:
[0010] A ceramic dielectric material includes a main material and an auxiliary material, wherein the main material is a (Sr, Ca, Ba) TiO3 system; the auxiliary material is Bi2O3·2TiO2; the components in the main material are mixed according to the following ratio:
[0011] SrCO3: 30%~40%;
[0012] CaCO3: 20%-30%;
[0013] BaCO3: 20%~30%;
[0014] TiO2: 10%~20%;
[0015] The addition amount of Bi2O3·2TiO2 is 1% to 5%.
[0016] Preferably, it includes SrCO3: 40%, CaCO3: 20%, BaCO3: 25%, TiO2: 10%, and Bi2O3·2T iO2: 5%.
[0017] Preferably, it includes SrCO3: 30%, CaCO3: 25%, BaCO3: 20%, TiO2: 15%, and Bi2O3·2T iO2: 10%.
[0018] Preferably, it includes CaCO3: 40%, BaCO3: 30%, TiO2: 20%, and Bi2O3·2TiO2: 10%.
[0019] Preferably, it includes SrCO3: 25%, CaCO3: 15%, BaCO3: 30%, TiO2: 20%, and Bi2O3·2T iO2: 10%.
[0020] Preferably, the auxiliary material Bi2O3·2TiO2 is prepared by premixing Bi2O3 and TiO2 in a molar ratio of 1:2, wet grinding and high-temperature calcination.
[0021] Another technical problem to be solved by the present invention is to provide a method for manufacturing the above-mentioned ceramic dielectric material, comprising the following steps:
[0022] Dissolve SrCl2, CaCl2, BaCl2, TiCl4 and NaOH in deionized water respectively to prepare TiCl4 icy water solution, strontium calcium barium mixed solution and NaOH solution;
[0023] The strontium calcium barium mixed solution is mixed with the TiCl4 ice water solution, and the NaOH solution is added and injected into the reactor for stirring to carry out a low-temperature liquid phase reaction to obtain a mixed suspension;
[0024] The mixed suspension after the reaction is transferred to a hydrothermal kettle for hydrothermal treatment;
[0025] After filtering, washing and drying, the main material (Sr0.78, Ca0.20, Ba0.02) TiO3 was obtained;
[0026] The auxiliary material Bi2O3·2TiO2 is prepared by wet mixing and solid phase method and mixed with the main material to form a ceramic dielectric material.
[0027] Preferably, the mixing ratio of the strontium calcium barium mixed solution and the TiCl4 ice water solution is 1:1, 1:2 or 2:1, and the added amount of NaOH is 1.2 to 6 times the reaction requirement of the strontium calcium barium mixed solution and TiCl4.
[0028] Another technical problem to be solved by the present invention is to provide a high-voltage chip-type multilayer ceramic capacitor prepared by the above-mentioned ceramic dielectric material.
[0029] Another technical problem to be solved by the present invention is to provide a method for preparing a high voltage chip type multilayer ceramic capacitor, comprising the following steps:
[0030] The ceramic medium material is uniformly mixed with an organic solvent, a dispersant, a plasticizer, a flow control agent, a defoaming agent and a wetting agent by high-energy ball milling to form a slurry, and a binder is added for secondary ball milling to prepare a high rheological property casting slurry;
[0031] The high rheological property tape-casting slurry is dry-casted through a tape-casting machine to form the nickel slurry required on the ceramic film;
[0032] Printing nickel paste on the dielectric film by using a screen printer to form a pattern with a specified design shape, and performing a lamination process;
[0033] The bar blocks are placed in a high-pressure hot isostatic hydraulic press for lamination to form densified bar blocks;
[0034] Use a high-speed cutting machine to cut the densified blocks into capacitor green sheets of uniform size;
[0035] Put the capacitor green sheets into the oven to remove the organic matter regularly;
[0036] According to the principle of sintering dynamics, the multilayer chip capacitor green sheet is sintered at high temperature to achieve the final ceramic structure;
[0037] Perform chamfering on capacitor chips;
[0038] The outer conductive electrode slurry is applied to both ends of the capacitor chip by a terminal sealing machine and solidified;
[0039] The copper layer is formed in a high temperature firing furnace;
[0040] Performing electrochemical surface treatment to sequentially cover with nickel layer and tin layer;
[0041] 100% electrical performance test is carried out by a fully automatic capacitor testing machine, and unqualified products are eliminated;
[0042] The qualified capacitor products are taped by a high-speed taping machine and packaged.
[0043] Compared with the prior art, the present invention has the following advantages:
[0044] The (Sr, Ca, Ba)TiO3 system is used as the main material, which significantly improves the dielectric constant and energy storage density, and can meet the performance requirements of ultra-high voltage multilayer capacitors; a variety of formulation solutions are provided, which can be customized according to different application needs, such as high dielectric constant, thermal stability, cost optimization and high-frequency performance, thereby enhancing the adaptability of the material; in the cost-optimized formula, by reducing the use of high-cost raw material SrCO3 and increasing the proportion of CaCO3, the production cost is effectively reduced, which is suitable for commercial large-scale production; the low-temperature liquid phase method combined with the hydrothermal treatment process helps to optimize the grain microstructure, improve the mechanical strength and thermal stability of the material, and enhance the reliability of the device.
[0045] The auxiliary material Bi2O3·2TiO2 is prepared by wet mixing and solid phase method, which allows the mixing ratio and calcination conditions to be adjusted according to experimental needs to ensure the controllability of the final product performance; the dielectric properties are optimized by rationally adjusting the ratio of BaCO3 and TiO2, which helps to reduce signal loss and is suitable for high-frequency applications; although BIT is a modifier with a small content, it can significantly improve the microstructure and performance of the material and enhance the overall quality of the product; through theoretical calculation and experimental optimization of the amount of NaOH added and the solution ratio, the high efficiency of the reaction and the high purity of the product are ensured, and the reliability and repeatability of the experiment are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Schematic diagram of the effect of reducing grain size on the energy storage performance of dielectric capacitors;
[0047] Figure 2 Schematic diagram of the effect of doping and solid solution modification on the energy storage performance of dielectric capacitors;
[0048] Figure 3 Schematic diagram of the effect of texture engineering on the energy storage performance of dielectric capacitors;
[0049] Figure 4 Schematic diagram of the effect of grain refinement by strategies such as doping and solid solution on the energy storage performance of dielectric capacitors;
[0050] Figure 5 Schematic diagram of energy storage performance of dielectric capacitors under different electric fields;
[0051] Figure 6 Surface morphology of the high-voltage chip multilayer ceramic capacitor sample 1812 and sample 2220 prepared by the present invention;
[0052] Figure 7 The dielectric properties test diagram of the high-voltage chip multilayer ceramic capacitor 1812 sample and 2220 sample prepared by the present invention under different room temperature conditions;
[0053] Figure 8 The ferroelectric performance test diagram of the high-voltage chip multilayer ceramic capacitor 1812 sample and 2220 sample prepared by the present invention under different room temperature conditions;
[0054] Fig. 9 This is the performance test diagram of 2220 sample under different external electric field conditions;
[0055] Fig.10 This is the performance test diagram of 1812 sample under different external electric field conditions;
[0056] Fig.11 A test report of a high-voltage chip-type multilayer ceramic capacitor sample prepared by the present invention;
[0057] Fig.12 A test record sheet of a high-voltage chip-type multilayer ceramic capacitor sample prepared by the present invention;
[0058] Fig.13 The electrical performance test record of the high-voltage chip-type multilayer ceramic capacitor sample prepared by the present invention. DETAILED DESCRIPTION
[0059] The specific implementation modes of the present invention are further described in detail to make the technical solutions of the present invention easier to understand and grasp.
[0060] Example 1
[0061] A multilayer chip ceramic capacitor ceramic dielectric, the dielectric ceramic material is prepared by compounding a main material, an auxiliary material, a modifier and a sintering aid. The main material of the dielectric ceramic material has a high energy storage density and a high breakdown voltage performance when the main material is a (Sr, Ca, 0Ba)TiO3 system. The auxiliary material is mainly Bi2O3·2TiO2. By compounding the main material, the auxiliary material and the modifier in proportion, the dielectric constant and the energy storage density are increased, and after being sintered into ceramic at a high temperature, the performance requirements of ultra-high voltage multilayer capacitors can be met.
[0062] In this embodiment, a high dielectric constant and low loss solution is adopted, specifically: strontium carbonate (SrCO3): 40% · calcium carbonate (CaCO3): 20% · barium carbonate (BaCO3): 25% · titanium trioxide (TiO2): 10% · Bi2O3 · 2T iO2 (BIT): 5% Description: This ratio is intended to achieve a high dielectric constant while reducing microwave losses through the high dielectric effect of SrCO3 and BaCO3 and the microstructure optimization of BIT.
[0063] Design of Microstructure of Ceramic Dielectric Layer in High Voltage Multilayer Capacitors
[0064] The precursor is prepared by low temperature liquid phase method and combined with hydrothermal treatment process to synthesize the main materials Sr0, Ca, Ba, TiO3;
[0065] (1) Preparation of solution: using analytically pure raw materials including SrCl2, CaCl2, BaCl2, TiCl4, NaOH and deionized water, and weighing them according to the ratio to prepare TiCl4 icy water solution, strontium calcium barium mixed solution and NaOH solution respectively;
[0066] (2) Low-temperature liquid phase reaction: The strontium calcium barium mixed solution and the TiCl4 ice water solution are measured in proportion, mixed and heated to 60°C, and the NaOH solution is heated to 80°C. The two heated solutions are then evenly injected into the reactor and stirred for 20 minutes to obtain a precursor as a mixed suspension.
[0067] Preparation of TiCl4 icy aqueous solution:
[0068] Raw materials: analytical grade TiC14 and deionized water.
[0069] Ratio: First, the total amount of TiCl4 required (in grams) must be determined. This value is usually determined based on the expected amount of final product and the stoichiometric ratio. For example, if a specific number of moles of product is required, the number of moles of TiCl4 required must be calculated based on the chemical reaction equation and further converted into the corresponding mass. Subsequently, the calculated amount of TiCl4 is slowly added to a sufficient amount of ice water. The volume ratio of TiCl4 to water is usually about 1:10 or more to prevent violent heat release and ensure that TiCl4 can be completely dissolved. During the entire preparation process, the solution must be maintained at a low temperature to effectively inhibit the hydrolysis reaction of TiCl4.
[0070] Preparation of strontium calcium barium mixed solution:
[0071] Raw materials: analytical grade SrCl 2, CaCl 2, BaCl 2 and deionized water.
[0072] Ratio: First, calculate the mass of SrCl 2, CaCl 2, and BaCl 2 according to the desired stoichiometric ratio and the requirements of the final product. For example, if the molar ratio of each element in the desired final product is 1:1:1, the corresponding mass needs to be calculated according to their respective molecular weights and dissolved in deionized water to ensure complete dissolution. The total mass can be determined according to the total volume of the desired final solution and the required concentration. Usually, the solution is kept transparent to facilitate observation of the reaction.
[0073] Preparation of NaOH solution:
[0074] Raw materials: analytical grade NaOH and deionized water.
[0075] Concentration standard: The concentration of NaOH solution can be set according to the specific experimental requirements. The common concentration range may be between 0.1M and 1M. For low-temperature liquid phase reactions, if strong alkaline conditions are required to promote the reaction, a 1M NaOH solution can be selected as the starting concentration. This means that there are 40g of NaOH per liter of solution (based on the molar mass of NaOH is 40g / mol). Be careful during the dissolution process because NaOH will release heat and is corrosive when dissolved.
[0076] Brief description of low temperature liquid phase reaction:
[0077] The prepared strontium calcium barium mixed solution and TiCl4 ice water solution are measured in a pre-designed ratio (the specific ratio needs to be determined based on the chemical reaction measurement and the purpose of the experiment), and slowly heated to 60°C after mixing. On the other hand, the 1M NaOH solution is heated to 80°C to improve its solubility and reaction activity. Subsequently, the two solutions are uniformly and slowly injected into a preheated reactor equipped with a stirring device, the reaction temperature is maintained, and stirred for 20 minutes to promote the reaction, and finally a precursor mixed suspension is obtained.
[0078] In order to provide specific examples of the ratio of strontium calcium barium mixed solution and TiCl4 ice water solution and the amount of NaOH solution added, we can set several common ratios and addition schemes. Here, we use "portions" as the basic unit, and the specific amount of each portion is flexibly adjusted according to actual needs and the scale of experimental equipment. The following are several possible ratio schemes, aiming to cover a wide range to explore the best conditions:
[0079] 1.1:1 ratio scheme: the strontium calcium barium mixed solution and the TiCl4 icy water solution are mixed in equal volumes or equal molar ratios. This ratio method is concise and clear, and is convenient for comparative analysis of the impact of a single variable.
[0080] 2.1:2 ratio scheme: In this scheme, the strontium calcium barium mixed solution accounts for a smaller proportion, and the TiCl4 ice water solution accounts for a larger proportion, which is suitable for exploring the effect of increasing TiCl4 content on product characteristics.
[0081] 3.2:1 ratio scheme: In contrast, this scheme increases the ratio of strontium calcium barium mixed solution to study its potential optimization effect on the performance of the final product.
[0082] 4.1:1:1 ternary ratio scheme: If the comprehensive influence of each component in the ternary system needs to be considered, the strontium, calcium, and barium mixed solutions can be mixed in equal proportions, and then mixed with TiCl4 ice water solution in a 1:1 ratio. In this case, the internal ratio also needs to be further explored in subsequent experiments.
[0083] Regarding the amount of NaOH solution added and its variation, in theory, it should be based on the stoichiometric requirements of the chemical reaction, that is, the number of moles of the corresponding hydroxide or composite oxide generated by the reaction with TiCl4 and other metal chlorides. However, in actual operation, in order to ensure complete reaction, NaOH is usually added in a slightly excessive amount.
[0084] Assuming a simplified model, that is, all metal chlorides react completely with NaOH to form the corresponding hydroxides, ignoring side reactions, the number of moles of NaOH should at least be equal to the total number of moles of chloride ions in the metal chlorides. However, in actual operation, considering factors such as reaction efficiency and possible by-product formation, the amount of NaOH added usually needs to be excessive.
[0085] For the case of "the mixing ratio of strontium calcium barium mixed solution to TiCl4 ice water solution is 1:3", if the total molar number of metal ions in the mixed solution is assumed to be X, then the molar number of TiCl4 is 3X (based on the ratio). Theoretically, the required molar number of NaOH is at least 4X (because 4 molecules of NaOH are required for each molecule of TiCl4, and the metal ions also require a corresponding amount of NaOH). However, the actual amount added may be 4X to 6X or even more, and the specific amount needs to be flexibly adjusted according to factors such as the completeness of the reaction observed in the experiment and the purity of the product.
[0086] In summary, when providing specific values, detailed calculations need to be performed based on the actual chemical reaction equation and the purpose of the experiment. It is recommended to set an initial excess coefficient (such as 1.2 times the theoretical value) based on theoretical calculations, and then gradually optimize through experiments to find the most appropriate amount of NaOH added. Each experiment should record the actual amount of all raw materials and the performance indicators of the product in detail, and gradually approach the optimal ratio using scientific methods.
[0087] (3) Hydrothermal treatment: The mixed suspension was transferred to a hydrothermal kettle and hydrothermalized at 180-220°C for 3-5 hours, then filtered, washed with deionized water, dried, and passed through a 40-mesh sieve to obtain the main material Sr0.78Ca0.20Ba0.02TiO3;
[0088] (4) The auxiliary material Bi2O3·2TiO2 is synthesized by wet mixing and solid phase method to prepare dielectric porcelain material.
[0089] The preparation process of the auxiliary material Bi 2O3·2TiO2 is briefly described as follows:
[0090] 1. Raw material preparation: Make sure that Bi2O3 and TiO2 are both analytical grade and the powder particle size is moderate to ensure that the two can be mixed evenly.
[0091] 2. Pre-mixing stage: Bi2O3 and TiO2 are weighed in a molar ratio of 1:2 and mixed evenly. This step can be dry mixed with the aid of a ball mill to increase the contact area and create favorable conditions for subsequent reactions.
[0092] 3. Wet mixing: Add the pre-mixed powder into an appropriate amount of deionized water and use a ball mill or mixer for wet grinding. The time is usually controlled between a few hours and dozens of hours to ensure that the powder is highly dispersed and evenly mixed.
[0093] 4. Drying and calcination: The wet material is dried to remove the water contained therein, and then placed in a muffle furnace for calcination. The calcination temperature and time need to be specifically set according to the formation temperature of Bi2O3·2TiO2, usually set in the range of above 800℃ to 1000℃, and last for several hours to ensure that the solid phase reaction can be fully carried out.
[0094] The corresponding relationship between the amount of the main material (Sr, Ca, Ba) TiO3 and the auxiliary material Bi2O3·2TiO2 is as follows:
[0095] When determining the dosage of Bi2O3·2TiO2, it is necessary to comprehensively consider its modification effect on the properties of dielectric porcelain (such as dielectric constant, quality factor Q value, thermal stability, etc.) and cost-effectiveness. The addition ratio of auxiliary materials is usually low to avoid excessive impact on the characteristics of the main material, but the specific ratio needs to be flexibly adjusted according to the experimental objectives.
[0096] Preliminary recommended ratio: If the total amount of (Sr, Ca, Ba) TiO3 system is 100 moles, the amount of the auxiliary material Bi 2O3·2TiO2 can be tried from 1% to 5% (molar ratio). For example, if a 3% addition amount is selected, for every 100 moles of (Sr, Ca, Ba) TiO3, 3 moles of Bi 2O3·2TiO2 need to be added.
[0097] Optimization strategy: In practical applications, the addition ratio of Bi2O3·2TiO2 can be gradually adjusted through a series of experiments, while monitoring the microstructure, dielectric properties and other key physical and chemical properties of the ceramic material. Usually, small-scale experiments are carried out first, such as sintering a small amount of samples, and then gradually expanded to the actual production scale after evaluating the performance.
[0098] Note: When adjusting the ratio, special attention should be paid to the fact that the addition of Bi2O3·2TiO2 may change the sintering behavior and microstructure of the main material. Therefore, the sintering parameters (such as temperature, time, atmosphere, etc.) need to be carefully adjusted to ensure that the ideal density and microstructure are achieved.
[0099] Through the above steps and principles, the dosage of Bi2O3·2TiO2 in the (Sr, Ca, Ba)TiO3 system can be systematically explored and optimized, and high-quality dielectric porcelain materials that meet specific performance requirements can be developed.
[0100] The manufacturing process of high voltage multilayer ceramic capacitors includes the following steps:
[0101] Slurry preparation, dry casting, screen printing, isostatic lamination, cutting, debinding, high temperature sintering, chamfering, end sealing, end burning (copper), surface treatment, test sorting, reliability test (military products), taping and packaging.
[0102] The specific process is described as follows:
[0103] (1) Slurry preparation
[0104] The ceramic powder is evenly mixed with the organic solvent, and appropriate amounts of dispersants, plasticizers, flow control agents, defoamers and wetting agents are added. The slurry is evenly mixed through high-energy ball milling. Subsequently, a binder is added and a secondary ball milling is performed to adjust the rheological properties of the slurry and prepare a high rheological properties casting slurry that meets production requirements.
[0105] (2) Dry Casting
[0106] The traditional tape casting process is optimized by using a high-precision tape casting machine and targeting the rheological properties of the prepared tape casting slurry. The film thickness is controlled by adjusting the distance between the tape casting machine scraper and the substrate; the film forming speed and quality are controlled by adjusting the scraper displacement speed; the thick film drying process is improved, and the heating program and insulation time are optimized to avoid cracking and other phenomena.
[0107] (3) Screen printing
[0108] A screen printer is used to form a pattern with a specified design shape on the dielectric diaphragm with nickel paste. The specific process includes: dry lamination of the lower cover, printing of the inner electrode, covering the inner electrode with a dielectric film, staggering the printer, repeating the steps of printing the inner electrode and covering the dielectric film until the designed number of layers is completed, and dry lamination of the upper cover.
[0109] (4) Lamination
[0110] Place the blocks into a high-pressure hot isostatic hydraulic press and set the process parameters to ensure that the blocks meet the density requirements under heavy pressure.
[0111] (5) Cutting
[0112] Using a high-precision, high-speed cutting machine, the densified blocks are cut into rectangular blocks of uniform size according to the cutting lines of the pattern to form capacitor green sheets.
[0113] (6) Debonding
[0114] The capacitor green sheets are placed in an oven (debinding box) with uniform temperature and large air volume, and the organic matter in the capacitor green sheets is regularly decomposed and discharged according to the set program.
[0115] (7) High temperature sintering
[0116] Combining the characteristics of the highly active powder produced and the principle of sintering dynamics, the atmosphere sintering method is used to sinter the multilayer chip capacitor blanks. The specific process is: slowly increase the temperature from room temperature to 1200℃ to remove solvents and adhesives; after the organic matter is completely removed, quickly increase the temperature to a higher temperature and keep it warm for a short time to sinter the product into porcelain.
[0117] (8) Chamfer
[0118] The capacitor and grinding medium are mixed in proportion and put into the chamfering machine for rolling grinding to ensure that the corners of the capacitor chip are smooth and the inner electrode is fully exposed to facilitate better connection with the outer electrode during sealing.
[0119] (9) End-capping
[0120] A high-precision sealing machine is used to evenly coat both ends of the chamfered capacitor chip with an outer conductive electrode slurry of uniform width and thickness, and the outer conductive electrode slurry is cured by drying and heating.
[0121] (10) Burning end (copper)
[0122] The capacitor after termination is placed in an atmosphere high temperature termination furnace, and the process parameters are set so that the outer conductive electrode slurry forms a copper layer that wraps the end of the product at high temperature and forms a phase fusion connection with the inner conductive electrode. The copper layer thickness is generally around 30 to 70 um, which can well lead out the inner electrode and ensure the reliability of the chip.
[0123] (11) Surface treatment
[0124] Using the principle of electrochemical reaction, a uniform nickel layer and tin layer are sequentially covered on the outer electrode of the capacitor after copper sintering. The nickel layer is generally 2-3um thick, which serves as a heat barrier to improve the product's resistance to thermal shock; the tin layer is generally 3-5um thick, which has good weldability and ensures good contact between the product and the external circuit.
[0125] (12) Testing
[0126] The surface treated high-voltage capacitors made of base metal materials are sorted by appearance and 100% electrical performance tested by a fully automatic capacitor testing machine. The test parameters include capacity, loss, withstand voltage and insulation resistance. Unqualified products are removed and qualified products continue to circulate.
[0127] (13) Reliability test (military products)
[0128] According to the product quality level or technical agreement requirements proposed by the customer, the reliability test is completed in accordance with the national military standard GJB192B-2011 test method requirements.
[0129] (14) Taping
[0130] The products that have passed the test / reliability test (military products) and meet customer requirements are quickly loaded into the paper tape / tape holes by a high-speed taping machine and rolled into a reel to form a finished product of base metal material high-voltage capacitor taping. If the number of military products is small, manual taping can be used.
[0131] (15) Packaging
[0132] The finished high-voltage capacitors made of base metal materials are packed into cartons as required, and the factory inspection report is attached, and then shipped to customers after packaging.
[0133] Example 2
[0134] The difference between this embodiment and embodiment 1 is that a high dielectric constant and low loss solution is adopted, specifically: strontium carbonate (SrCO3): 30%·calcium carbonate (CaCO3): 25%·barium carbonate (BaCO3): 20%·titanium trioxide (TiO2): 15%·Bi2O3·2TiO2 (BIT): 10%.
[0135] Description: The proportion of TiO2 and BI T is increased, and their advantages in improving thermal stability and enhancing mechanical strength are utilized, which is suitable for components that need to be used in harsh environments.
[0136] Example 3
[0137] The difference between this embodiment and embodiment 1 is that a cost-optimized solution is adopted, specifically: calcium carbonate (CaCO3): 40%·barium carbonate (BaCO3): 30%·titanium trioxide (TiO2): 20%·Bi2O3·2TiO2 (BIT): 10%.
[0138] Description: Reduce the use of SrCO3, which is more expensive, and increase the proportion of CaCO3 to reduce costs. At the same time, improve the overall performance through BIT assistance, which is suitable for large-scale commercialization.
[0139] Example 4
[0140] The difference between this embodiment and embodiment 1 is that a high frequency performance optimization scheme is adopted, specifically: strontium carbonate (SrCO3): 25%·calcium carbonate (CaCO3): 15%·barium carbonate (BaCO3): 30%·titanium trioxide (TiO2): 20%·Bi2O3·2TiO2 (BI T): 10%.
[0141] Description: Focus on improving the performance of materials under high-frequency conditions, by increasing the ratio of BaCO3 to TiO2, combined with the fine-tuning effect of BIT, to optimize dielectric properties and reduce signal loss. Notes: In the actual production process, the formula needs to be adjusted according to the specific application requirements, and the optimal sintering conditions, including temperature, time, atmosphere, etc., need to be determined through experiments. The purity, particle size distribution and uniform mixing degree of the material have an important influence on the final ceramic performance, so the raw materials should be strictly screened and pretreated before preparation. As an additive, although the content of BIT is small, it may significantly affect the microstructure and performance of the material, so it needs to be accurately weighed and the addition ratio controlled.
[0142] Experimental example
[0143] Research on methods to improve the energy storage performance of dielectric capacitors
[0144] Reducing grain size: See Figure 1 As shown, the grain size decreases → the breakdown electric field increases, the saturation polarization is delayed → the energy storage density and energy storage efficiency increase. The methods to achieve this include doping, solid solution and process control.
[0145] Doping and solid solution modification: see Figure 2 As shown, reducing the grain size increases the breakdown electric field, reduces polarization loss, and reduces residual polarization → the effective energy storage density and energy storage efficiency increase.
[0146] Texture Engineering: See Figure 3 As shown, synthesize template → prepare textured film by casting → reduce electro-induced strain and improve breakdown resistance.
[0147] See also Figure 4 As shown in the figure, the grains are refined by doping, solid solution and other strategies to prepare MLCC with good co-firing properties.
[0148] The energy storage efficiency test of the high-voltage multilayer ceramic capacitor of this scheme is as follows Figure 5 As shown, the specific data is shown in Table 1 below.
[0149] Table 1
[0150] electric field Effective energy storage density Total energy storage density Energy storage efficiency A(X) B(Y) C(Y) D(Y) E Wr W xiaolv B*100 / C 100 0.263 0.264 99.62121 200 2.709 2.795 96.92308 300 8.769 9.115 96.20406 400 10.613 11.101 95.604 500 12.164 12.851 94.65411 570 13.137 13.94 94.2396
[0151] It can be seen from the above table that the high-voltage chip multilayer ceramic capacitor of this scheme has good energy storage performance.
[0152] See also Figure 6 As shown in the figure, it is a sample picture of a high-voltage chip multilayer ceramic capacitor prepared by this scheme. The Ni electrode in the sample has good continuity, the elements of the 2220 series samples are evenly distributed, the overall density of the ceramic body is good and the thickness is relatively uniform.
[0153] See also Figure 7-8 As shown in the figure, the dielectric and ferroelectric performance test diagram of the high-voltage chip multilayer ceramic capacitor sample prepared by this scheme, the thickness and area of the film are 2220 (60μm, 1.787cm 2 ),1812(40μm,1.116cm 2 ), where the capacitance of the 2220 sample at room temperature and at 1kHz is 564.7nF, the dielectric constant is 21414, and the dielectric loss is 0.013, while the capacitance of the 1812 sample is 441.4nF, the dielectric constant is 17868, and the dielectric loss is 0.012. The temperature coefficients of the two samples change by more than 50% within the range of 250°C.
[0154] See also Figure 9-10 As shown, after the external electric field of sample 2220 and sample 1812 reaches 6kV / cm and 9kV / cm (36V), the electrodes cannot be pressurized.
[0155] See also Figure 11-13 As shown, there are performance test record reports and photos of the high-voltage chip multilayer ceramic capacitor porcelain material prepared by this scheme.
[0156] Of course, the above are only typical examples of the present invention. In addition to these, the present invention may also have many other specific implementations. Any technical solutions formed by equivalent replacement or equivalent transformation fall within the scope of protection required by the present invention. Of course, the above are only typical examples of the present invention. In addition to these, the present invention may also have many other specific implementations. Any technical solutions formed by equivalent replacement or equivalent transformation fall within the scope of protection required by the present invention.
Claims
1. A ceramic dielectric material, characterized in that , including main materials and auxiliary materials, wherein the main material is (Sr, Ca, Ba)TiO3 system; the auxiliary material is Bi2O3·2TiO2; the components in the main material are mixed according to the following ratio: SrCO3: 30%~40%; CaCO3: 20%-30%; BaCO3: 20%~30%; TiO2: 10%~20%; The addition amount of Bi2O3·2TiO2 is 1% to 5%.
2. The ceramic dielectric material according to claim 1, characterized in that Including SrCO3: 40%, CaCO3: 20%, BaCO3: 25%, TiO2: 10%, Bi2O3·2TiO2: 5%.
3. The ceramic dielectric material according to claim 1, characterized in that Including SrCO3: 30%, CaCO3: 25%, BaCO3: 20%, TiO2: 15%, Bi2O3·2TiO2: 10%.
4. The ceramic dielectric material according to claim 1, characterized in that Including CaCO3: 40%, BaCO3: 30%, TiO2: 20%, Bi2O3·2TiO2: 10%.
5. The ceramic dielectric material according to claim 1, characterized in that Including SrCO3: 25%, CaCO3: 15%, BaCO3: 30%, TiO2: 20%, Bi2O3·2TiO2: 10%.
6. The ceramic dielectric material according to claim 1, characterized in that The auxiliary material Bi2O3·2TiO2 is prepared by premixing Bi2O3 and TiO2 in a molar ratio of 1:2, wet grinding and high-temperature calcination.
7. A method for manufacturing the ceramic dielectric material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Dissolve SrCl2, CaCl2, BaCl2, TiCl4 and NaOH in deionized water respectively to prepare TiCl4 icy water solution, strontium calcium barium mixed solution and NaOH solution; The strontium calcium barium mixed solution is mixed with the TiCl4 ice water solution, and the NaOH solution is added and injected into the reactor for stirring to carry out a low-temperature liquid phase reaction to obtain a mixed suspension; The mixed suspension after the reaction is transferred to a hydrothermal kettle for hydrothermal treatment; After filtering, washing and drying, the main material (Sr0.78, Ca0.20, Ba0.02)TiO3 was obtained; The auxiliary material Bi2O3·2TiO2 is prepared by wet mixing and solid phase method and mixed with the main material to form a ceramic dielectric material.
8. The method of claim 7, wherein: The mixing ratio of the strontium calcium barium mixed solution and the TiCl4 icy water solution is 1:1, 1:2 or 2:1, and the added amount of NaOH is 1.2 to 6 times the reaction requirement of the strontium calcium barium mixed solution and TiCl4.
9. A high voltage chip-type multilayer ceramic capacitor made of the ceramic dielectric material according to any one of claims 1 to 8.
10. A method for preparing a high voltage chip type multilayer ceramic capacitor, characterized in that: The following steps are involved: The ceramic medium material is uniformly mixed with an organic solvent, a dispersant, a plasticizer, a flow control agent, a defoaming agent and a wetting agent by high-energy ball milling to form a slurry, and a binder is added for secondary ball milling to prepare a high rheological property casting slurry; The high rheological property tape-casting slurry is dry-casted through a tape-casting machine to form the nickel slurry required on the ceramic film; Printing nickel paste on the dielectric film by using a screen printer to form a pattern with a specified design shape, and performing a lamination process; The bar blocks are placed in a high-pressure hot isostatic hydraulic press for lamination to form densified bar blocks; Use a high-speed cutting machine to cut the densified blocks into capacitor green sheets of uniform size; Put the capacitor green sheets into the oven to remove the organic matter regularly; According to the principle of sintering dynamics, the multilayer chip capacitor green sheet is sintered at high temperature to achieve the final ceramic structure; Perform chamfering on capacitor chips; The outer conductive electrode slurry is applied to both ends of the capacitor chip by a terminal sealing machine and solidified; The copper layer is formed in a high temperature firing furnace; Performing electrochemical surface treatment to sequentially cover with nickel layer and tin layer; 100% electrical performance test is carried out by a fully automatic capacitance testing machine, and unqualified products are eliminated; The qualified capacitor products are taped by a high-speed taping machine and packaged.